2022
DOI: 10.3390/v14091853
|View full text |Cite
|
Sign up to set email alerts
|

Emerging Genotype IV Japanese Encephalitis Virus Outbreak in New South Wales, Australia

Abstract: The detection of a new and unexpected Japanese encephalitis virus (JEV) outbreak in March 2022 in Australia, where JEV is not endemic, demanded the rapid development of a robust diagnostic framework to facilitate the testing of suspected patients across the state of New South Wales (NSW). This nascent but comprehensive JEV diagnostic service encompassed serological, molecular and metagenomics testing within a centralised reference laboratory. Over the first three months of the outbreak (4 March 2022 to 31 May … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
15
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 17 publications
(15 citation statements)
references
References 26 publications
0
15
0
Order By: Relevance
“…The incubation period after a mosquito bite is 5–15 days. The virus replicates in local Langerhans cells and keratinocytes, and regional lymph nodes, after which it is carried by the lymphatic systemic into the thoracic duct and bloodstream [ 5 , 78 ]. JEV is neurotropic resulting in meningoencephalitis in approximately 1% of cases [ 79 ].…”
Section: Japanese Encephalitis Virusmentioning
confidence: 99%
See 3 more Smart Citations
“…The incubation period after a mosquito bite is 5–15 days. The virus replicates in local Langerhans cells and keratinocytes, and regional lymph nodes, after which it is carried by the lymphatic systemic into the thoracic duct and bloodstream [ 5 , 78 ]. JEV is neurotropic resulting in meningoencephalitis in approximately 1% of cases [ 79 ].…”
Section: Japanese Encephalitis Virusmentioning
confidence: 99%
“…Viral shedding can be prolonged: for example, ZIKV RNA may be detectable for long periods in urine (median 24 days) and semen (median 25 days, but up to 370 days) [ 132 ]. Targeted NAAT assays carry higher diagnostic specificity but lower sensitivity due to short-lived viremia in many of these infections [ 5 , 125 ]. Loop-mediated isothermal amplification (LAMP)-based methodologies have been used for the detection of some flaviviruses such as JEV in resource-limited settings [ 133 ].…”
Section: Laboratory Diagnosismentioning
confidence: 99%
See 2 more Smart Citations
“…As of 22 October 2022, over 40 human JE cases, with seven fatal cases, have been reported [ 41 ]. The outbreak of JEV was first identified in swine and subsequently in humans, mosquitoes, and sentinel chickens [ 42 ]. Genetic analysis of the virus associated with the epidemics in 2021 and 2022 indicated that the virus was GIV JEV [ 38 , 40 , 43 ].…”
Section: Introductionmentioning
confidence: 99%